Compliance with Social Distancing, Facial Mask, Sanitizer/Hand Washing against COVID-19 - Kayastha, Jyoti; Kayastha, Prakash; Nepali, Rabin; Kayastha, Usha (Journal of Institute of Medicine Nepal, 2024)
Introduction: At the end of 2019, a novel coronavirus spread rapidly, resulting in a global pandemic. Many countries have employed various nonpharmaceutical interventions, including social distancing, mask use, and sanitizer/hand hygiene measures (SMS). Previous studies have reported that compliance with these preventive measures varied widely. So, this study was conducted to assess the compliance with social distancing, mask use, and sanitizer/soap use measures in Biratnagar. Methods : This was a descriptive cross-sectional study conducted from September to November 2021 among 310 individuals at a hospital, supermarket, and vegetable market in Biratnagar. Using convenience sampling, mask use, social distancing, and hand hygiene was observed. Individuals not following SMS measures were asked about their reasons for non-compliance. Results : Among 310 individuals, 84.19% used masks, but only 86.97% of them wore them correctly. Surgical masks were used by 93.1%, while 6.9% used cloth masks. Social distancing was followed by 20.96%, and 31.29% used hand sanitizer. Common reasons for noncompliance included discomfort with masks, cost of sanitizer, lack of handwashing facilities, absence of social distancing markings, and poor adherence by others. Conclusion : Compliance of face mask was relatively high, while compliance with social distancing and sanitizer use was low highlighting the need for improved public awareness, better infrastructure, and stricter enforcement. In low-resource settings like Nepal, the continued promotion of SMS measures is essential for managing current health threats and preventing future outbreaks of respiratory illnesses.